Integrating ESG and Financial Resilience to Enhance Bank Performance: Evidence from Systemically Important Banks in Indonesia - Puspitorini, Jayanti; Siswanti, Indra (IJOSMAS, 2025)
This study aims to examine the influence of Environmental, Social, and Governance (ESG) factors on financial performance through Financial Resilience as a mediating variable in Indonesian banking sector. The research investigates the effect of environmental, social, and governance dimensions on financial performance, with Financial Resilience serving as a mediating variable in KBMI 3 and KBMI 4 banks listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. A quantitative explanatory approach was applied using panel data regression and path analysis via EViews version 13. The sample consists of 13 banks using saturated sampling technique, resulting in 65 observations. The findings reveal that social and governance factors have a significant positive impact on financial performance, while environmental factors show a negative and insignificant effect. All three ESG dimensions demonstrate positive and significant influences on financial resilience. Furthermore, Financial Resilience significantly and positively affects financial performance. The mediation analysis indicates that Financial Resilience successfully mediates the relationship between social and governance factors with financial performance, but fails to mediate the environmental-financial performance relationship. This study contributes to the theoretical literature by enhancing insights into the integration of ESG practices and financial resilience in shaping banking performance, particularly in the context of Indonesia's large-scale banking institutions (KBMI 3 and 4).